2019
DOI: 10.1021/acs.orglett.9b02448
|View full text |Cite
|
Sign up to set email alerts
|

Isocyanide Multicomponent Reactions on Solid-Phase-Coupled DNA Oligonucleotides for Encoded Library Synthesis

Abstract: Isocyanide multicomponent reactions play a prominent role in drug discovery. This chemistry has hardly been investigated for compatibility with DNA-encoded combinatorial synthesis. The Ugi, Ugi-azide, and Groebke−Blackburn− Bienayméreactions are well-tolerated by DNA on the solid phase and show a broad scope. However, an oxadiazole-forming variant of the Ugi reaction caused DNA depurination, requiring a more stable hexathymidine DNA for encoded library synthesis. Cheminformatic analysis revealed that isocyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 53 publications
1
47
0
5
Order By: Relevance
“…Heteroaromatic anilines had to be excluded from the Povarov reaction and substituted b-ketoesters and ureas for the Biginelli reaction are only scarcely available. In agreement with an earlier library analysis, 25 we observed that application of different synthesis methods (here Diels-Alder, Povarov and Biginelli reactions) led to only partially overlapping chemical space from common DNA-coupled starting materials.…”
Section: Cheminformatics Analysis Of Simulated Encoded Heterocycle LIsupporting
confidence: 91%
See 2 more Smart Citations
“…Heteroaromatic anilines had to be excluded from the Povarov reaction and substituted b-ketoesters and ureas for the Biginelli reaction are only scarcely available. In agreement with an earlier library analysis, 25 we observed that application of different synthesis methods (here Diels-Alder, Povarov and Biginelli reactions) led to only partially overlapping chemical space from common DNA-coupled starting materials.…”
Section: Cheminformatics Analysis Of Simulated Encoded Heterocycle LIsupporting
confidence: 91%
“…† Our chemically very stable adapter oligonucleotide hexT 7 and three different decamer DNA oligonucleotides (TC 8, ATC 9, and ATGC 10) were incubated with three aqueous acids, as well as 33 metal salts and 20 organocatalysts dissolved in dry organic solvents. To reect plausible reaction conditions, 24,25 the catalysts were incubated with DNA strands at a 200-fold reagent excess for 22 hours at ambient temperature. Aer washing steps and standard DNA cleavage from solid support we quantitated and characterized DNA damage by RP-HPLC and MALDI-TOF mass spectrometric analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCRs proved to be compatible with solid-phase synthesis and can be effective for creating scaffold diversity with a low synthetic cost ( Rivera et al, 2021 ). In 2019, Brunschweiger’s team reported isocyanide-involved MCRs for DNA-encoded combinatorial synthesis ( Kunig et al, 2019 ). This concept has great potential to be applied for fluorescence labeling or other derivatizations of DNA with isocyanides as well as to introduce an isocyano group into DNA.…”
Section: Methods To Introduce the Isocyano Group Into Biomacromoleculesmentioning
confidence: 99%
“…10a) 85 . In cooperation with Dömling's group 84 , the same team also exploited the versatility of isocyanide-based MCRs 10 to produce DNA-coupled heterocycles such as oxadiazoles and tetrazoles (Fig. 10a).…”
Section: Functionalized Water-stable Parallel β-Sheetsmentioning
confidence: 99%